Early Virus Clearance and Delayed Antibody Response in a Case of Coronavirus Disease 2019 (COVID-19) With a History of Coinfection With Human Immunodeficiency Virus Type 1 and Hepatitis C Virus. (9th April 2020) - Zhao, Juanjuan; Liao, Xuejiao; Wang, Haiyan; Wei, Lanlan; Xing, Mingzhao; Liu, Lei; Zhang, Zheng
Abstract: The effect of host immune status on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection remains unknown. Here, we report the first case of coronavirus disease 2019 (COVID-19) with human immunodeficiency virus type 1 (HIV-1)/hepatitis C virus coinfection, who showed a persistently negative SARS-CoV-2 RNA test but delayed antibody response in the plasma. This case highlights the influence of HIV-1–induced immune dysfunction on early SARS-CoV-2 clearance.